2018
DOI: 10.1097/gox.0000000000001849
|View full text |Cite
|
Sign up to set email alerts
|

Silicone Migration and Late Hematoma following Silicone Implant Rupture: Case Report and Literature Review

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…The second most common place for free silicone migration is regional lymph nodes (axillary lymph nodes), and silicone aggregates in lymph nodes can also mimic malignant processes [ 7 , 8 ]. Occasionally, free silicone travels to distant regions (arm/forearm, thoracic cavity, abdominal wall, legs, back) [ 9 , 10 ]. In order to avoid these complications, it is of crucial importance to detect implant rupture as soon as possible and to remove or replace a ruptured implant [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…The second most common place for free silicone migration is regional lymph nodes (axillary lymph nodes), and silicone aggregates in lymph nodes can also mimic malignant processes [ 7 , 8 ]. Occasionally, free silicone travels to distant regions (arm/forearm, thoracic cavity, abdominal wall, legs, back) [ 9 , 10 ]. In order to avoid these complications, it is of crucial importance to detect implant rupture as soon as possible and to remove or replace a ruptured implant [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…it is thought that silicone can migrate through hematogenous or lymphatic routes [ 31 ]. Various distant migration sites of silicone from breast are reported, including the upper extremity, groin and thoracic cavity [ 32 , 33 ]. Lymphatic migration of silicone in the groin lymph node is considered as a potential route for dissemination.…”
Section: Discussionmentioning
confidence: 99%
“…This comparison of late breast hematomas with chronic subdural hematomas was described by Roman [23] in 2005 even. In the past year, 2018, two cases of late hematoma were reported: Kim et al [31] explained its development as a consequence of severe capsular contracture, while Dean et al [32] described a case of silicone extravasation that may have led to chronic lymphocytic granulomatous reaction and a consequent recurrent acute-on-chronic hematoma. Grippaudo et al [3] in 2013 reported a singular case of late hematoma developed 2 years after breast surgery, due to mechanical friction in the space between the two layers of a double capsule.…”
Section: Discussionmentioning
confidence: 99%